2015
DOI: 10.3389/fcell.2015.00021
|View full text |Cite
|
Sign up to set email alerts
|

Atypical centrioles during sexual reproduction

Abstract: Centrioles are conserved, self-replicating, microtubule-based, 9-fold symmetric subcellular organelles that are essential for proper cell division and function. Most cells have two centrioles and maintaining this number of centrioles is important for animal development and physiology. However, how animals gain their first two centrioles during reproduction is only partially understood. It is well established that in most animals, the centrioles are contributed to the zygote by the sperm. However, in humans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 152 publications
(223 reference statements)
0
59
0
Order By: Relevance
“…Early zygotes in C. reinhardtii also undergo dramatic changes in their cytoskeleton. Unlike the case in animals, where paternal but not maternal centrioles are contributed to zygotes (Avidor-Reiss et al, 2015), in C. reinhardtii, both parental basal bodies (structurally similar to centrioles) and flagella are retained initially in zygotes but eventually are disassembled and rebuilt during germination (Cavalier-Smith, 1976). Nonetheless, investigation of conserved zygotically up-regulated cytoskeletal proteins such as LF5 and SF-assemblin may shed light on more general mechanisms involved in controlling the dynamic behavior of flagella/cilia and basal bodies during cellular remodeling and life cycle transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Early zygotes in C. reinhardtii also undergo dramatic changes in their cytoskeleton. Unlike the case in animals, where paternal but not maternal centrioles are contributed to zygotes (Avidor-Reiss et al, 2015), in C. reinhardtii, both parental basal bodies (structurally similar to centrioles) and flagella are retained initially in zygotes but eventually are disassembled and rebuilt during germination (Cavalier-Smith, 1976). Nonetheless, investigation of conserved zygotically up-regulated cytoskeletal proteins such as LF5 and SF-assemblin may shed light on more general mechanisms involved in controlling the dynamic behavior of flagella/cilia and basal bodies during cellular remodeling and life cycle transitions.…”
Section: Discussionmentioning
confidence: 99%
“…When present, the PC in both vertebrate groups is short [0.3µm in the ostrich (Soley, 1993) and approximately 0.5µm in mammals as in somatic cells (Agircan et al, 2014)], lies partially within the implantation fossa at the base of the nucleus, and displays the characteristic pinwheel arrangement of microtubular triplets embedded in a ring of moderately electron-dense material (Avidor-Reiss et al, 2015;Sathananthan, 2012;Soley, 8 1993) (Fig. 2b).…”
Section: Ultrastructure Of the Centriolar Complexmentioning
confidence: 99%
“…For successful in vitro fertilisation (IVF) a thorough knowledge of sperm abnormalities was required and, based on patient studies, a number of obvious centriolar defects were identified that adversely affected fertility (Afzelius, 1996;Chemes, 2012;Chemes and Sedo, 2012;Moretti and Collodel, 2012;Zamboni, 1992). With the advent of intracytoplasmic sperm insemination (ICSI) it became clear that more subtle changes to the composition of the centrosome at a molecular level, not reflected as obvious structural anomalies, could adversely affect successful zygote formation 3 and subsequent embryogenesis (Avidor-Reiss et al, 2015;Chemes, 2012;Rawe, 2003, 2010;Sathananthan, 2012;Sathananthan et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations